The Relationship of Anxiety, Confidence, and Motivation to the Performance of Volleyball Referees: A Correlation Study - Nurfani Nurfani; Setya Rahayu; Bambang Priyono (STKIP Muhammadiyah Kuningan, 2022)
The purpose of this study was to analyze the relationship between anxiety, self-confidence, and motivation to the performance of the referees of volleyball associations throughout Indonesia, West Nusa Tenggara province. This study uses a correlational method with a quantitative approach. The population is 45 referees, sampling using total sampling. The research variable was the performance of the volleyball referee as the dependent variable and anxiety, self-confidence, and motivation as the independent variables. The data analysis technique used a linearity test and product-moment correlation. The results of this study are 1) a low relationship between anxiety and the performance of volleyball referees. 2) moderate relationship between confidence and the performance of volleyball referees. 3) a strong relationship between motivation and the performance of volleyball referees. 4) moderate relationship between anxiety and self-confidence with the performance of volleyball referees. 5) a strong relationship between self-confidence and motivation with the performance of volleyball referees. 6) a strong relationship between anxiety and motivation with the performance of volleyball referees. 7) a strong relationship between anxiety, self-confidence and motivation with the performance of volleyball referees. The conclusion of this study is to increase the confidence of referees through training programs in the psychological (mental) realm that are integrated into the training program with an understanding of the rules of the game regularly. This effort is made to improve the quality of the performance of volleyball referees.